Vineyard practices reduce the incidence of Aspergillus spp. and alter the composition of carposphere microbiome in grapes (Vitis vinifera L.) - Testempasis, S. I.; Papazlatani, C. V.; Theocharis, S.; Karas, P. A.; Koundouras, S.; Karpouzas, D. G.; Karaoglanidis, G.S. (Frontiers in Microbiology, 2023)
Going through the new transitioning era of the "European Green Deal", the search for alternative, non-chemical, disease control methods is essential. Aspergillus bunch rot is considered one of the most important diseases of grapevines resulting in severe yield losses and, major qualitative deterioration of grape products due to the production of mycotoxins. We investigated, in a two-year field study, the impact of agronomic practices like defoliation to enhance grape microclimate (DF), pruning method to reduce grape bunch density (LBD), and irrigation cut-off (NIR), at three developmental stages of grapevine (Pea size berry, Veraison, and Harvest), on (i) grape composition (titratable acidity, pH, and total soluble solids), (ii) on the frequency of occurrence of Aspergillus on grape berries and (iii) on the overall composition of grape carposphere microbiome. The density of Aspergillus on grape berries was significantly reduced by the applied management practices (DF, LBD, NIR). Amplicon sequencing analysis showed that both the phenological stage and the agronomic practices employed (particularly NIR and DF) imposed significant changes in the α-diversity and β-diversity of the grape carposphere bacterial and fungal communities. The NIR, LBD, and DF treatments which supported lower Aspergillus populations, network analysis revealed negative co-occurrence patterns between Aspergillus and several bacterial genera (Streptococcus, Rhodococcus, Melitangium) reported to have antifungal properties suggesting potential natural attenuation mechanisms for the control of Aspergillus. Overall, our study (i) showed that the application of halting of irrigation and thinning of leaves and grape bunches, reduce the occurrence of Aspergillus and hence the incidence of Aspergillus Bunch rot disease and (ii) identified preliminary evidence for interactions of Aspergillus with members of the epiphytic grape bacterial communities that might be involved in the suppression of Aspergilli, an observation which will be further pursued in following studies in the quest for the discovery of novel biological control agents.